1988
DOI: 10.1111/j.1600-0773.1988.tb00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Renal Function in Cadmium‐Intoxicated Rats

Abstract: Changes in renal function, Na+-K+-ATPase activity and PAH transport system in kidney cortex were studied in rats treated with cadmium. Subcutaneous injections of CdCl2 (2 mg Cd/kg.day) for 16 days induced a marked polyuria and a hyposthenuria. These changes were accompanied by increase in urinary protein, glucose, urea, calcium, phosphate, chloride and potassium excretions. The change in urine flow was proportional to the change in total osmotic solute excretion. Creatinine excretion and TcH2O remained unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 31 publications
3
15
0
1
Order By: Relevance
“…It seems that the duration of treatment and the doses used were not enough to produce significant renal damage. However, these results are in homogeny with other similar studies [37,38]. Dudley et al [39] showed that hepatic injury occurs prior to renal damage following Cd administration, which confirms that over long period of Cd exposure, the hepatic release of Cd-metallothionein with its subsequent translocation to kidney produces renal damage.…”
Section: Discussionsupporting
confidence: 81%
“…It seems that the duration of treatment and the doses used were not enough to produce significant renal damage. However, these results are in homogeny with other similar studies [37,38]. Dudley et al [39] showed that hepatic injury occurs prior to renal damage following Cd administration, which confirms that over long period of Cd exposure, the hepatic release of Cd-metallothionein with its subsequent translocation to kidney produces renal damage.…”
Section: Discussionsupporting
confidence: 81%
“…Pathological changes in the kidneys due to cadmium have been noted frequently in many experiments (Bernard et al, 1992;Chin and Templeton, 1992;Groten et al, 1991;Hewitt et al, 1991;Itokawa et al, 1974Itokawa et al, , 1978Kim et al, 1988;Ś wiergosz et al, 1998;Waalkes et al, 1992b). It is known that there is a clear difference in the toxicity in rats fed inorganic cadmium (CdCl 2 ) from those fed cadmium bound to MT.…”
Section: Kidneymentioning
confidence: 95%
“…This nephrotoxicity causes reabsorptive and secretory dysfunction of the renal tubule. The main signs include proteinuria, ion losses, glucosuria, aminoaciduria, and polyuria (1,2,21,24,29,31). Experimental chronic intoxication with Cd 2ϩ has been performed at various doses over several weeks (9,30,48) and causes a Fanconi-like syndrome with predominant tubular dysfunction that develops into renal failure (47,48).…”
mentioning
confidence: 99%